Signs of popular culture in the performance of the Iraqi theater actor (Journal of the College of Basic Education, 2019)
The theater dealt with many topics over the ages of simulating the variables of life and imposed by the burdens on the human, to explain this existence and its data within its system, using theories, laws and philosophies a lot through the invasion of many of the terms employed by theater theorists according to the course of the era and its significance and language, The study of linguistics and semantics and the science of human behavior to reach a clear meaning of what this existence and simulated through the interpretation of scattered signs hidden and apparent, to be representative of one of these signs employed by the theater alongside many of the signsWhich is acquired from the outside world, which we find has established the foundations of the community of the past and present and future constituent of the popular culture as a definition identity for each environment through (his culture and tone and habits and values ​​and behavior) to find that there is re-employment of this popular culture in his theatrical proposals in response to the negative phenomena that lasted Societies by many social and political variables to refer us to a system of popular brands inherited over time employed by the actor to create an interactive and interactive relationship with the recipient through his audio and visual tags. The research tracks include four chapters:Chapter I: The methodological framework of the research problem and its need. The methodological framework also includes the importance of the research, its objectives, its limits, and the definition of terms (marks, performance).Chapter Two: The theoretical framework includes two topics, and previous studies, as follows:The first topic: the concept of popular culture in social discourse.The second topic: signs of popular culture in the performance of the actor.The fourth topic: previous studiesThus, the researcher developed through the theoretical framework the research indicators on two levels (the sound system) and the (physical system).The third chapter dealt with the sample of the research in the light of the criteria of the theoretical framework, to be selected the following sample:A play / curfew / directed by Muhannad HadiThe third chapter ends with a summary of the search results.While the fourth chapter contains the conclusions reached by the researcher.Finally, the researcher proved the list of sources and the research summary in English.